Atrial endomysial fibrosis is associated with sex, atrial fibrillation, heart failure and age in cardiac surgery patients: results from the Catch-Me consortium. (19th May 2022) - Winters, J; Isaacs, A; Zeemering, S; Casadei, B; Fabritz, L; Guasch, E; Mont, L; Hatem, S; Kirchhof, P; Verheule, S; Schotten, U
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): Horizon 2020 Background: Risk factors for atrial fibrillation (AF), such as ageing, heart failure and AF itself, enhance AF propensity partly by inducing atrial fibrosis. Atrial endomysial fibrosis, a type of reactive fibrosis occurring between cardiomyocytes, impairs transverse conduction in rapid atrial pacing animal models. The factors underlying transcriptional regulation of endomysial fibrosis are largely unknown. Objective: To examine the contributions of age, sex, AF and heart failure to the development of endomysial fibrosis in the context of concurrent pathologies. To study genome-wide transcriptional changes associated with endomysial fibrosis in human left and right atrial appendage biopsies (LAA, n=95; RAA, n=76). Methods: An algorithm for automated quantification of endomysial fibrosis following staining with wheat germ agglutinin (WGA) was employed. Linear mixed models were constructed to determine endomysial fibrosis quantity as a function of AF, heart failure, sex, age and four principal components that accounted for potential confounding effects of other clinical characteristics. RNA sequencing was used to study expression changes in the atrial transcriptome associated with endomysial fibrosis. Results: Sex, persistent AF, heart failure and age were independently associated with endomysial fibrosis. We identified hundreds (LAA: 386, RAA: 311) of RNA transcripts associated with endomysial fibrosis. None of these associations were independent from the clinical phenotypes. However, explorative gene set enrichment analysis identified association of endomysial fibrosis with gene sets involved in extracellular matrix organization, immune response, cell motility, developmental processes, cardiac muscle contraction and proteostasis in LAA while in RAA only gene sets regulating contractile function were enriched. Conclusion: Besides AF, female sex, age and heart failure are associated with endomysial fibrosis in the atria. While abundance of none of the differential genes were independently associated with endomysial fibrosis, gene set enrichment analysis suggests an involvement of extracellular matrix organization, immune response, cell motility, developmental processes and cardiac muscle contraction in endomysial fibrosis.